Appropriation multisensorielle du rythme du français : codage rythmique visuel d’extraits filmiques au sein d’un dispositif hybride - Nadia Bacor (Corela)
In this contribution, we propose to address the multi-sensory learning of the French rhythm by developing a colour coding and symbols of film excerpts in order to acquire French rhythm. The aim will therefore be to provide theoretical and pedagogical insight into the teaching-learning of the French as a Foreign Language (FLE) rhythm in language classes for non-specialist language learners of FLE. First, we will present the theoretical foundations on which our pedagogical approach is based and then we will put into practice rhythmic coding with examples from an experiment as part of an action-research project through a hybrid device aimed at the acquisition of French pronunciation at level C1 of the Common European Framework of Reference for Languages (CEFRL) in a university-level setting.